HUBUNGAN MOTIVASI, REWARD, DAN PUNISHMENT DENGAN PERILAKU TENAGA KERJA DALAM MENJALANKAN PROGRAM STOP DI PT X PASURUAN - Risky Wira Putri; Tri Martiana (Universitas Airlangga, 2018)
Occupational Safety and Health (OSH) was an important benchmark in industrial activities in order to achieve maximum productivity and avoid losses that harm the company and the workers themselves. The number of work accidents in Indonesia awas still high. Mostly cause by human factors. One effort to prevent accidents that was STOP program with approach to human factor. Commitment of workforce in running STOP program has not reached 100% and STOP card collection still need to be reminded so that need to be improved by knowing factors related to worker behavior in running STOP program. One of them was by ABC analysis. This research type was observational with cross sectional research design with sample number 50 workers. Data collection by observation, give questionnaire, and interview to HSE. Methods of data analysis using spearmen correlation test. Independent variables in this study were reward and punishment. The dependent variable in this study was the behavior of the workers in running the STOP program. The result of statistical test shows that there was a relationship between reward (p = 0.000), and punishment (p = 0.039) with workers behavior in running STOP program. The conclusion of this research was gift reward and punishment can be increase behavior of the workers in running STOP program so reward and punishment can be used as consideration for program intervention.Keywords: ABC analysis, punishment, reward, STOP program